SECURITY RESEARCH THAT ALLOW FOR THE COEVOLUTIONARY PROTECTION OF NETWORKS - Rakesh Kumar (International Journal of Multidisciplinary Research and Studies, 2020)
A cyber-attack can be described as any hostile act designed to compromise the supply, privacy or integrity of a network. But, for the purposes of this lesson, distinguish between computer network exploitation (CNE), which is typically associated with the theft of records, and PC community attacks (CNA), which typically involve disruption of information structures or are associated with destruction. Yes, not critical. Many organizations within the cyber security community make a distinction between computer network exploitation (CNE), which is generally related to information theft, and computer network attacks (CNA). Consequently, for the sake of convenience, those two different styles of malicious hoaxes can be lumped together under the umbrella term "cyberattack". In the early days of the Internet, completely laptop-based attacks on the general public took the form of computer worms and viruses.